A coleção mossoroense e a construção dos mitos: Dix-Sept Rosado, o herói imolado - Nóbrega, Alessandro Teixeira (2007)
This research comprises a study on the values and ideals attributed to Dix-sept Rosado, by the Coleção Mossoroense journal. Local researchers demonstrate how the Coleção Mossoroense constructs an image of Mossoró, forming in the members of the city an identity with the place, a social cohesion or creating one forms to see and to say about the Mossoró city. The Coleção Mossoroense, through Vingt-un Rosado together with its family, established a form of seeing and identifying of the Mossoró s population with the city, just because it associated and it was, at the same time, a movement at the same time social (civic parties for example), political (the domination of the Rosado s family) and cultural (the books and theatrical parties about the city). The conjunction of the Coleção Mossoroense as and with a social movement, cultural and political was capable to establish a social identity, a subjective constituent . With this background, it was possible to make a study of the image attributed to Dix-sept Rosado, by the Coleção Mossoroense, through an analysis of the inherent discourse in the works by Bakhtin (1989) and Bourdieu (2000), of and on Dix-sept Rosado in the Coleção Mossoroense based on. The image of Dix-sept Rosado was constructed by the Coleção Mossoroense after its death, and the responsible for this was Vingt-un Rosado, which was the chief-editor of the Coleção Mossoroense up to 2006, year of its death. The Coleção Mossoroense built an image of Dix-sept Rosado as an enterprising man, progressive and innovator, of great capacity of leadership and oratory (a conductor of the crowds ), popular and charismatic, an honest and dynamic politician. This image made by the Coleção Mossoroense, although when enhancing in surplus the qualities of Dix-sept Rosado have as objective to transmit an image of a heroic personage, it has some relation with the reality. Dix-sept Rosado was a man identified with its locality. This can resemble a regional nationalism. The attitudes of Dix-sept Rosado must be understood inside of a broader social context, of a time marked by the populist politics. Qualities also appreciated and developed inside of a specific historical context and determined both national and locally. The Coleção Mossoroense enhances the qualities of Dix-sept Rosado so that the current politicians of the Rosado s family can establish a link of continuity in its contemporary political practice